Improving local results: Fusing community design and community development. Issue 5 (19th October 2016) - Moomaw, Suzanne Morse
Abstract: Many community design and community development practices are rooted in the social upheaval of the 1960s and the political milieu that followed. These areas of practice are situated within a broad range of organizations, institutions, and individuals committed to addressing social, political, economic, and environmental inequities. Despite a plethora of efforts to improve community conditions by public, not-for-profit, and private sectors, challenges persist such as poverty, racial inequities, and environmental degradation. This article argues that a more intentional integration of community design into community development practices could generate new options for identifying solutions and achieving scale on systemic issues by engaging community members in an integrative design-based approach to community development solutions.